Two-channel microwave power switch construction on the basis of electrically active semiconductor structures - Lavrich, Yu. N.; Plaksin, S. V.; Kris, V. Ya.; Pogorelaya, L. M.; Sokolovskiy, I. I. (Technology and design in electronic equipment, 2014)
When constructing the fast-acting two-channel microwave switch, it is difficult to use p–i–n-diodes due to inertia of processes in such structures at change of control voltage polarity for providing of deep modulation. Under the practical realization of the microwave switches on p–i–n-diodes, the requirements to the operating speed of the output signal and to the frequency range are in conflict with each other.The optimum decision may be to use the bulk (without p–n-junctions) two-electrode semiconductor structures based on the effect of intervalley transfer of electrons (TEDs) and chalcogenide-glass-semiconductors (CGS-diodes) with high operating speed and stability at considerable power levels in the wide frequency band.The paper presents the construction of the two-channel microwave switch in the three-centimetre range of wave lengths based on bulk semiconductor structures having negative differential conductivity (NDC) of N- and S-type, and realizing the functions of peak power modulator on a TED-diode and the switch on a CGS-diode respectively.